Bone Staples Provide Favorable Primary Stability in Cortical Fixation of Tendon Grafts for Medial Collateral Ligament Reconstruction: A Biomechanical Study. Issue 7 (2nd July 2021) - Glasbrenner, Johannes; Deichsel, Adrian; Raschke, Michael J.; Briese, Thorben; Frank, Andre; Herbort, Mirco; Herbst, Elmar; Kittl, Christoph
Background: The use of the interference screw (IFS) for the cortical fixation of tendon grafts in knee ligament reconstruction may lead to converging tunnels in the multiligament reconstruction setting. It is unknown whether alternative techniques using modern suture anchor (SA) or bone staple (BS) fixation provide sufficient primary stability. Purpose: To assess the primary stability of cortical fixation of tendon grafts for medial collateral ligament (MCL) reconstruction using modern SA and BS methods in comparison with IFS fixation. Study Design: Controlled laboratory study. Methods: Cortical tendon graft fixation was performed in a porcine knee model at the tibial insertion area of the MCL using 3 different techniques: IFS (n = 10), SA (n = 10), and BS (n = 10). Specimens were mounted in a materials testing machine, and cyclic loading for 1000 cycles at up to 100 N was applied to the tendon graft, followed by load-to-failure testing. Statistical analysis was performed using 1-way analysis of variance. Results: There were no statistical differences in elongation during cyclic loading or peak failure load during load-to-failure testing between BS (mean ± standard deviation: 3.4 ± 1.0 mm and 376 ± 120 N, respectively) and IFS fixation (3.9 ± 1.2 mm and 313 ± 99.5 N, respectively). SA fixation was found to have significantly more elongation during cyclic loading (6.4 ± 0.9 mm; P < .0001) compared with BS and IFS fixation and lower peak failure load during ultimate failure testing (228 ± 49.0 N; P < .01) compared with BS fixation. Conclusion: BS and IFS fixation provided comparable primary stability in the cortical fixation of tendon grafts in MCL reconstruction, whereas a single SA fixation led to increased elongation with physiologic loads. However, load to failure of all 3 fixation techniques exceeded the loads expected to occur in the native MCL. Clinical Relevance: The use of BS as a reliable alternative to IFS fixation for peripheral ligament reconstruction in knee surgery can help to avoid the conflict of converging tunnels.